Analisis Personal Higiene dan Pengetahuan dengan Kejadian Skabies pada Santri di Pondok Pesantren Al-Ikhwan Kota Pekanbaru tahun 2017 - Nila Puspita Sari; Sella Mursyida (Jurnal Kesehatan Komunitas, 2018)
One of the problems faced by students of Al-Ikhwan Islamic Boarding School is personal hygiene, such as skin hygiene, hands, nails, genitalia, feet and clothes. Bad habits in maintaining personal hygiene are one cause of health problems in the form of scabies disease. Scabies is one of the most common skin diseases. This study aimed to determine the analysis of environmental sanitation and personal hygiene with the incident of scabies at Al-Ikhwan boarding school Pekanbaru City. This research used the method of analytical description and cross sectional design. The population in this study were santriwati which amounted to 143 students. The sample in this study were 83 students with the inclusion criteria being students who were willing to become a respondent in class VII until IX. Sampling technique used simple random sampling. Chi Square statistical test results for personal hygiene p = 0.047, POR (95% CI) = 3.010 (1.119-8.098) means that there was a relationship between personal hygiene and the occurrence of scabies at Al-Ikhwan Islamic Boarding School and there was also a relationship between knowledge and scabies at Al-Ikhwan Islamic Boarding School with a value of p = 0.011, POR (95% CI) = 0.254 (0.095-0.681). Suggestion for the management of Islamic boarding school to provide additional lessons and counseling about the pattern of hygienic behavior and personal hygiene to the santri in order to generate a high awareness of good health behavior in preventing transmission of scabies diseases.